Personification in Cats (musical) by Andrew Lloyd Webber (Journal of the College of Basic Education, 2025)
The musical Cats by Andrew Lloyd Webber is a brilliant example of personification in musical theatre. Taking inspiration from T.S. Eliot’s Old Possum’s Book of Practical Cats, the musical recreates a lively cat society, endowing them with human-like traits and feelings. This paper demonstrates the use of personification in Cats (musical) by Andrew Lloyd Webber and how these characters are presented on the stage by giving these creatures humanistic traits such as the ability to dance, sing, walk on two, think, etc. The methodology used in this paper is a qualitative critical analysis utilising personification in the play, by focusing on main points such as anthropomorphism, personification, musical theatre, mythology and mythical deities, such as Bastet, the themes of acceptance and mirroring. Furthermore, it allocates how these techniques are applied in the musical of Cats; resulting in a cohesive analysis for characters, themes and images. Andrew Lloyd Webber’s Cats is a timeless examination of human nature that uses personification to elevate a conventional tale about cats. The musical enhances its emotional effect and provides timeless reflection on society and personality by granting these adored animal characters with human characteristics. Giving entities humanistic qualities is called Anthropomorphism, which is an actual application in Webber’s Cats.